Una mirada a la Sociología en Medellín - -CEO-, Centro de Estudios de Opinión; Serna Angel, Alba Lucía; Tobón, Alonso; Ruiz Restrepo, Jaime (La Sociología en sus Escenarios, 2009)
Abstract. By the beginning of the sociology in Medellin, it’s about a program with a strong content of Catholic social doctrine guided by the self-taught sociology, mostly lawyers and some priests trained in Europe, not necessarily sociologists who, from different ideological perspectives contributed to the awareness of the plight of the most vulnerable social sectors. This germ, coupled with the general situation of social crisis which has prevailed both in the country and in Latin America and the rise of revolutionary movements in several countries of the continent, were driving to the linking of many students of this program with social struggles every time More radical and internally great pressure towards changing the curriculum and toward participation in the university Resumen. Por el origen de la Sociología en Medellín, se trata de un programa con un fuerte contenido de doctrina social católica orientado por autodidactas de la sociología, en su mayoría abogados y algunos sacerdotes formados en Europa, no necesariamente sociólogos, quienes, desde perspectivas ideológicas distintas contribuían en la sensibilización hacia la suerte de los sectores sociales mas desprotegidos. Este germen, unido a la situación general de crisis social que se vivía tanto en el país como en América Latina y al auge de movimientos revolucionarios en varios países del continente, fueron conduciendo a la vinculación de muchos estudiantes de este programa con luchas sociales cada vez mas radicales e internamente a una gran presión hacia la modificación del curriculo y hacia la participación en el gobierno universitario.